Internet Network Analysis on Local Provider X Using QoS Method - Abidin, Mohammad Mansyur (Intellithings Journal, 2025)
Local Provider X is an internet service provider at the village level with a focus on supporting household internet needs with 2-5 device connections per home. There are At Least 55 home connections in this provider. With the increasing number of users, the service quality of the Local Provider X internet network needs to be tested to maintain service quality. The testing was carried out using the the Quality of Service (QoS) method with the Action Research approach. Four main parameters were tested, namely throughput, packet loss, delay, and jitter. The assessment used was the TIPHON standardization developed by the European Telecommunications Standards Institute (ETSI). The test results revealed that the throughput value was in the range of 395.60 - 755.42, which had an average index of 2 with the "Average" category. The packet loss value was in the range of 0.01 - 1.89 with an index of 4 and the "Very good" category. The delay value was in the range of 9.64 - 20.70, which had an index of 4 and the "Very Good" category. The jitter value is in the range of 12.04 - 21.94, which has an index of 3 and the category "Good.". Based on the evaluation of all parameters, the overall QoS Index for Local Provider X’s internet network was calculated at 81.25%.